2022
DOI: 10.1159/000527860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperferritinemia on Functional Outcome in Acute Ischemic Stroke Patients with Admission Hyperglycemia

Abstract: <b><i>Introduction:</i></b> Hyperferritinemia, presented as elevated serum ferritin level, is an indicator of high iron status which plays roles in secondary brain injury after acute ischemic stroke (AIS). However, the effects of hyperferritinemia and poor outcomes remain uncertain. Additionally, admission hyperglycemia quite frequently accompanies AIS patients, which is associated with unfavorable outcome. Thus, we aimed to investigate the effects of hyperferritinemia on 3-month and 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…However, the relationship did not exist after adjusting confounders in all patients with IS. 35 A study proceeding from a 6-month follow-up has also indicated a similar conclusion. 36 However, contrasting results have been reported.…”
Section: Discussionmentioning
confidence: 66%
“…However, the relationship did not exist after adjusting confounders in all patients with IS. 35 A study proceeding from a 6-month follow-up has also indicated a similar conclusion. 36 However, contrasting results have been reported.…”
Section: Discussionmentioning
confidence: 66%
“…23 However, recently it has been shown that hyperferritinemia is associated with poor functional outcomes only in hyperglycemic patients, which might suggest that factors related to oxidative stress might play an additional role in the mechanism of brain damage in acute ischemia. 24 Transferrin binds free iron, acting as a free radical scavenger and is downregulated during inflammation. Higher levels of transferrin decrease the risk of stroke, 25 correlate inversely with clinical status, and may be protective against early deterioration.…”
mentioning
confidence: 99%